Pesan Dakwah K.H. Hasyim Asy’ari pada Film Sang Kiai - Fahmi Rusydi; Suryadi Firdaus (STID DI AL-HIKMAH, 2016)
In this study, the authors used a qualitative approach method of data collection is done through observation of the film The Kiai as the primary data and interviews with two (2) speakers who met the study criteria that the film director Kiai (Mr. Rako Prijanto) and character actor KH Hasyim Ashari (Ikranegara) as well as a literature review of secondary data. The analysis used, among others, the analysis of the content (Content Analysis) to analyze the verbal message while semiotic analysis to analyze non-verbal messages. Propaganda messages contained in the film The Kiai includes three categories: message aqidah of 8 scenes, the message of shari'ah as many as 36 scenes and 60 scene moral message.